Omalizumab (Xolair) in Children with Atopic Dermatitis: A Review Article - Javad Ghaffari; Negar Ghaffari (Mazandaran University of Medical Sciences, 2018)
Context: Atopic dermatitis is a chronic skin disease in children. The prevalence of eczema is up to 30% in the world. Omalizumab (Xolair) is a monoclonal antibody that blocks the serum IgE. The aim of this study is to review the effect of Xolair in children with atopic dermatitis. Evidence Acquisition: The data was searched in PubMed, Scopus, and Embase with keywords: atopic dermatitis, eczema, children, pediatrics, Xolair, and Omalizumab. The inclusion criteria included articles related to use of Xolair in children with atopic dermatitis, under the age of 20 years old, as well a both full text and brief articles. The exclusion criteria were purely adult cases who had taken systemic immunosuppressive drugs and abstract article. There was no time limitation for our search. Results: After evaluating all data and a total of 124 searched articles, we found 8 eligible articles for this review. All of them had severe atopic dermatitis except 2 cases, which had moderate severity. Serum IgE level was increased in all patients. Only one of those studies included a control group. All patients were associated with other allergic disorders such as asthma and allergic rhinitis. Conclusions: Omalizumab (Xolair) is a safe drug, which decreases serum IgE level, scoring atopic dermatitis, as well as clinical manifestations in all of severe atopic dermatitis. However, in order to approve it, we need future clinical trial studies with control group.